Bacterial Vaginosis, Candidiasis Vulvalginitis, and Suspected Gonorrhea in Pregnant Women with Risk Factor for Sexually Transmitted Infection from Her Husband - Wakhdatul Lubbi, Yusniya Farida; Nurrakhma Arum, Siti; Hevy Purwaningtyas, Nuretha; Gina Prabawati, Nirmala; Dasa Novita, Khuznita (Family Medicine Department, Faculty of Medicine, Brawijaya University, 2023)
Bacterial vaginosis is a reproductive system infection that causes a variety of symptoms. This condition can be caused by a variety of risk factors, including sexually transmitted infection from her husband. This case was detected in a Malang City primary health care. An in-depth history is collected to identify risk factors, followed by a home visit to detect risk factors. We shall explore the role and use of family medicine in cases of bacterial vaginosis in this case report. Because of the complicated interplay of biopsychosocial variables, comprehensive and holistic treatment is required.